SCYPHOSTEGIA BORNEENSIS STAPF*Anatomy of Stem and Leaf in Relation to its Taxonomic Position - METCALFE, C. R. (Research Center for Biology, 1956)
From an examination of anatomical characters it appears that the genus Scyphostegia is not related to Monimiaceae and Moraceae but represents a separate family related to Flacourtiaceae.